If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9X-8=4+8X
We move all terms to the left:
9X-8-(4+8X)=0
We add all the numbers together, and all the variables
9X-(8X+4)-8=0
We get rid of parentheses
9X-8X-4-8=0
We add all the numbers together, and all the variables
X-12=0
We move all terms containing X to the left, all other terms to the right
X=12
| 14.75+0.12(x+3)=15.25+0.11x | | 20x+x^2=-25 | | 9=2/5m | | k8+7=18 | | -2=2÷(p+-18) | | -52=12m-10+m | | Y-0.25x=-1 | | 25×2^x=25600 | | 120÷f=1.2 | | 6(f-4)=6 | | 3x-4=7×+12 | | 1525=-15x+400 | | 5(x+1=-5 | | 6+-2x=11 | | 4x+4=2x+34 | | (-18+p)÷2=-2 | | 9)10=4-y | | (x+1)x6=36 | | 16x+9-2x=9 | | -4j=-2j+10 | | 300-10x=410 | | I3(x-4)I+7=16 | | 4+0.09x=10 | | s*7+22=169 | | 5(3z-3=30 | | 192=0.09x+12 | | 3x+34=9 | | 0.05x+25=125 | | 10=√20x | | 8)3(-4-2c)=-24 | | 2^4x=4096 | | -02/3x=12 |